2004
DOI: 10.3136/fstr.10.35
|View full text |Cite
|
Sign up to set email alerts
|

The Solubilization of Unheated Cattle Achilles Tendon with Actinidin under Neutral and Acidic Conditions

Abstract: The solubilization of cattle achilles tendon with actinidin was investigated under neutral and acidic conditions. 1.43 to 1.92 and 0.97 to 3.19% of collagen were solubilized by treating the cattle achilles tendon with actinidin at 20˚C at pH 6.0 and 3.3, respectively. Furthermore, SDS-polyacrylamide gel electrophoresis of reaction mixtures with actinidin demonstrated that actinidin degraded the tendon into collagen subunit chain, ␤-and ␣-chain and peptide fragments of various sizes at 20˚C at pH 6.0 and 3.3. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…We speculate that actinidin degraded connective tissue structures that in turn have resulted in weakening of connective tissue and increased heat solubility of collagen. In agreement, hydrolysis of type I collagen by actinidin10 and increased solubility of collagen after incubation of tendon with actinidin8 have been reported. Furthermore, kiwifruit juice decreased the shear force of connective tissue and increased liberation of collagen‐related peptides upon heat‐treatment at 50 and 70 °C 9…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We speculate that actinidin degraded connective tissue structures that in turn have resulted in weakening of connective tissue and increased heat solubility of collagen. In agreement, hydrolysis of type I collagen by actinidin10 and increased solubility of collagen after incubation of tendon with actinidin8 have been reported. Furthermore, kiwifruit juice decreased the shear force of connective tissue and increased liberation of collagen‐related peptides upon heat‐treatment at 50 and 70 °C 9…”
Section: Discussionsupporting
confidence: 83%
“…Actinidin did not produce off‐flavours or odours in the meat and no surface ‘mushiness’ was found. Collagen is affected by the enzyme as incubation of bovine Achilles tendon with purified actinidin either at neutral or acidic pH increased the solubility of collagen 8. Also, cross‐linked collagen β‐ and γ‐chains isolated from beef shank were converted to α‐chains after incubation in kiwifruit juice at acidic pH 9.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this phenomenon is still not known. Wada and others 2004, have reported solubilization of cattle Achills tendon using actinidin. The reason for the difference in the results of 2 studies might be related to many factors including purity of the enzyme preparation, incubation time, method of incubation, and other unknown factors.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a kiwifruit marinade has long been known to tenderize meat, and several studies have confirmed this (Aminlari, Shekarforoush, Gheisari, & Golestan, 2009;Christensen et al, 2009;Gheisari, Shekarforoush, & Aminiari, 2008;Lewis & Luh, 1988a;Wada, Hosaka, Nakazawa, Kobayashi, & Hasegawa, 2004;Wada, Suzuki, Yaguti, & Hasegawa, 2002;Wada, Yamaguti, Koremura, & Hasegawa, 2003). The use of a kiwifruit marinade has long been known to tenderize meat, and several studies have confirmed this (Aminlari, Shekarforoush, Gheisari, & Golestan, 2009;Christensen et al, 2009;Gheisari, Shekarforoush, & Aminiari, 2008;Lewis & Luh, 1988a;Wada, Hosaka, Nakazawa, Kobayashi, & Hasegawa, 2004;Wada, Suzuki, Yaguti, & Hasegawa, 2002;Wada, Yamaguti, Koremura, & Hasegawa, 2003).…”
Section: Applicationsmentioning
confidence: 94%